Digital media and intergenerational migration: Nannies from the global south. Issue 2 (3rd April 2017) - Kim, Youna
ABSTRACT: Based on long-term ethnographic research on global nannies in Paris, this study explores the possibilities and limitations of digital media use for minorities, given that more and more young women from the global south engage with digital media. It will argue that transnational relations and practices are not necessarily and inevitably a progressive process, but pose new yet often risky opportunities more than freedoms, or foster a normalization of risk.